1983
DOI: 10.1037/0278-7393.9.3.486
|View full text |Cite
|
Sign up to set email alerts
|

The source of relatedness effects on naming latency.

Abstract: In this article we investigate the effects of semantic relatedness on the time to say a word. Two studies are reported: In the first the subject named pairs of pictures, and in the second the subject read aloud pairs of words. The probability of related pairs was varied in both studies. Semantic relatedness had a large effect on the time to name a picture but not on the time to read a word aloud. The effect of relatedness was greater when the probability of a related pair was high, but this was not because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
1
3

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 12 publications
8
104
1
3
Order By: Relevance
“…An additional point that should be noted here is the replication of the frequency effect for picture naming observed by Oldfield and Wingfield (1965) and Huttenlocher and Kubicek (1983); pictures with frequently used names were named more rapidly and more accurately than pictures with infrequently used names. Moreover, Wingfield (1968) showed that the frequency effect was not due to the time needed to recognize the object, suggesting that this effect would appear to be located in the phase of lexical access.…”
Section: Discussionmentioning
confidence: 99%
“…An additional point that should be noted here is the replication of the frequency effect for picture naming observed by Oldfield and Wingfield (1965) and Huttenlocher and Kubicek (1983); pictures with frequently used names were named more rapidly and more accurately than pictures with infrequently used names. Moreover, Wingfield (1968) showed that the frequency effect was not due to the time needed to recognize the object, suggesting that this effect would appear to be located in the phase of lexical access.…”
Section: Discussionmentioning
confidence: 99%
“…Kroll and Potter (1984), however, did find a (24-ms) frequency effect in an object decision experiment. Although the word frequency effect in naming has repeatedly been confirmed (Humphreys, Riddoch, & Quinlan, 1988;Huttenlocher & Kubicek, 1983), these studies did not add to a further refinement of the locus discussion. The models that-were used distinguished only between a concept and a word, and the frequency effect was usually adduced to the word level.…”
Section: Picture Namingmentioning
confidence: 99%
“…These names became the target label for each picture, resulting in a mean name agreement of 88% (SD = 13.4) for the experimental items. To control for frequency effects upon naming latencies (e.g., Huttenlocher & Kubicek, 1983;Jescheniak & Levelt, 1994), object category pairs (e.g., HARP-BANJO) were matched on name frequency using the English word form frequencies per million from the CELEX database (Baayen, Piepenbrock, & van Rijn, 1993). One picture from each of the 16 experimental pairs was then assigned to one of two item lists, arbitrarily called Set A and Set B, as shown in Appendix A.…”
Section: Experiments 1 Methodsmentioning
confidence: 99%